The use of score for neonatal acute physiology perinatal extention II (SNAPPE II) in predicting neonatal outcome in neonatal intensive care unit - Mia R A; Risa Etika; Agus Harianto; Fatimah Indarso; Sylviati M Damanik (Indonesian Pediatric Society Publishing House, 2016)
Background Scoring systems which quantify initial risks have an important role in aiding execution of optimum health services by pre- dicting morbidity and mortality. One of these is the score for neonatal acute physiology perinatal extention (SNAPPE), developed by Richardson in 1993 and simplified in 2001. It is derived of 6 variables from the physical and laboratory observation within the first 12 hours of admission, and 3 variables of perinatal risks of mortality. Objectives To assess the validity of SNAPPE II in predicting mor- tality at neonatal intensive care unit (NICU), Soetomo Hospital, Surabaya. The study was also undertaken to evolve the best cut-off score for predicting mortality. Methods Eighty newborns were admitted during a four-month period and were evaluated with the investigations as required for the specifi- cations of SNAPPE II. Neonates admitted >48 hours of age or after having been discharged, who were moved to lower newborn care <24 hours and those who were discharged on request were excluded. Re- ceiver operating characteristic curve (ROC) were constructed to derive the best cut-off score with Kappa and McNemar Test. Results Twenty eight (35%) neonates died during the study, 22 (82%) of them died within the first six days. The mean SNAPPE II score was 26.3+19.84 (range 0-81). SNAPPE II score of the nonsurvivors was significantly higher than the survivors (42.75+18.59 vs 17.4+14.05; P=0.0001). SNAPPE II had a good performance in predicting overall mortality and the first-6-days mortality, with area under the ROC 0.863 and 0.889. The best cut- off score for predicting mortality was 30 with sensitivity 81.8%, specificity 76.9%, positive predictive value 60.0% and negative predictive value 90.0%. Conclusions SNAPPE II is a measurement of illness severity which correlates well with neonatal mortality at NICU, Soetomo Hospital. The score of more than 30 is associated with higher mortality